The essayistic culture between fabulation and academic essayish: some notes (Educação e Pesquisa, 2020)
The purpose of this paper is to discuss the constitutive elements of the essayistic culture that emerged in the 16th and 17th centuries, and how this culture has been retrieved in contemporary university environments. Appropriated both by the supporters of academic essayish — authors interested in fighting the productivism rage that took over academic research — and by the educational production inspired by the thinking of Gilles Deleuze and Félix Guattari, interested in building a poetics of research with a more fabulatory tone. The argumentation of this essay will proceed as follows: first, we will present the emergence of an essayistic culture in Europe throughout the 16th and 17th centuries, paying attention to the fact that the essay does not arise only from the pen of some renowned authors, from Michel de Montaigne to Francis Bacon; rather, it is configured as a way of thinking concerned with apprehending and experiencing the European crisis of conscience in a different way from that pursued by rationalism. Next, we will try to understand how this essayistic culture recovers a certain idea of fabulation that, in some way, will resonate in Gilles Deleuze’s thought as a belief in the world. Finally, we will conclude with some brief notes on how this essayistic culture echoes in the discussions promoted both by the adepts of academic essayish, in their struggle against productivism, and by the recent deleuzian and deleuzo-guattarian educational production.